Melatih Fokus dan Kesabaran Anak Autisme dengan Metode Meronce Gelang Manik-manik - Raudhatul Jannah; Fajar Utama Ritonga (Jurnal Pelayanan dan Pengabdian Masyarakat Indonesia, 2024)
Children with special needs are children who require special attention both physically and mentally due to developmental disorders during their growing years. There are several types of children with special needs, one of which is autism. Autism is a neurodevelopmental disorder that makes it difficult for children with autism to perform daily activities such as communication and interaction. This practice is designed for children with special needs with the aim of controlling their emotions and training their concentration using the method of threading bead bracelets. During a two-month implementation period, the results showed that this method successfully trained the patience and concentration of children with autism.